Analysis of The Application of Environmental Cost Accounting at PT. Buana Wiralestari Mas - Debana Maharani, Anggun; Yenni Samri Juliati Nasution; Hendra Harmain (Dinasti International Journal of Economics, Finance & Accounting, 2024)
PT Buana Wiralestari Mas is a private company engaged in the plantation and palm oil processing plant, which is a subsidiary of PT Sinar Mas, emphasizes its responsibility to the environment by managing environmental costs arising from its operational activities. Impairment or costing is how PT Buana Wiralestari Mas recognizes environmental costs and allocates that value to environmental stewardship. Environmental costs are calculated using rupiah values that are comparable to past value practices. Overhead costs, transportation, and auxiliary materials are examples of production costs included in the presentation of environmental costs. In practice, the company has not prepared a special report on environmental costs, but has included these costs in the general financial statements. The results show that PT Buana Wiralestari Mas faces several challenges related to environmental cost accounting, including the expansion of disclosure and improvement of the cost measurement system.